Procedural fine is a remedial sanction for arbitrary usage of procedural rights - Abdullh, Hadi Mohamed; Ali, Sirwan Rauf (Journal of Legal and Political Studies, 2022)
The ruling to impose fine for arbitrary use of procedural rights is considered as one of the recognized principles in the modern procedural laws. It is a monetary sanction provided to public treasury as a compensation for the damage harmed the society resulted from the arbitrary use of procedural rights. This is aiming to deter the person who exercises such right in an abusive or improper way. Imposing fine has a dual role; it is a sanction that does not intend to provide a remedy for the private damage harmed the related parties or the third party. It rather intends to provide a solution for the public damage that harmed the public interest. Therefore, the fine that imposed as a sanction to respond the arbitrary use of procedural rights is accomplished through the ruling to impose a monetary amount that should be paid for the interest of the public treasury. This ruling is different with the ruling of paying compensation, being a sanction that has different function compared to the function of latter sanction. Even though the importance of the procedural fine and its practical benefits, it has not fulfilled its function to provide a solution for increased unjustified lawsuits. For that purpose, this research aims to study the provisions of procedural fine as a remedial mean of arbitrary exercise of procedural rights, explaining the attitude of law and jurisprudence related to that issue. Moreover, it aims to explain the factors that contributed to impede this means in Iraq and the way to combat it.
Keywords: Procedural fine; procedural laws; private damage; third party; jurisprudence